2018
DOI: 10.1097/bot.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

Helical Blade or the Integrated Lag Screws: A Matched Pair Analysis of 100 Patients With Unstable Trochanteric Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
0
23
1
2
Order By: Relevance
“…TAD value of CMN is considered a key indicator to predict postoperative cut-out complications. Patients with a TAD < 25 mm were less likely to encounter screw cut-outs complication [24]. In our study and average TAD was 20.3 mm and associated with fewer failures than previous studies.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…TAD value of CMN is considered a key indicator to predict postoperative cut-out complications. Patients with a TAD < 25 mm were less likely to encounter screw cut-outs complication [24]. In our study and average TAD was 20.3 mm and associated with fewer failures than previous studies.…”
Section: Discussioncontrasting
confidence: 42%
“…Inserting the PFNA blade can also compact the cancellous bone and provide additional stability [12]. As for unstable proximal femeral frature, PFNA and InterTAN nail are effective CMN options [23,24]. TAD value of CMN is considered a key indicator to predict postoperative cut-out complications.…”
Section: Discussionmentioning
confidence: 99%
“…The search yielded 308 potentially relevant reports, and 117 remained after the duplicate articles were deleted, of which 57 were excluded by preliminary screening; further careful screening of the full text excluded 51 articles leaving 9 for detailed evaluation. Nine studies ( n = 1332 patients) are published between January 2013 and December 2019 that fulfilled the inclusion and exclusion criteria, including 2 RCTs and 7 observational studies [ 14 , 20 27 ]. A total of 1332 patients were relatively evenly distributed in PFNA ( n = 681 patients) and InterTAN nail groups ( n = 651 patients), and the proportion of the two surgical procedures in A1, A2, and A3 fractures is 88/80, 479/460, and 113/112, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All the results were robust except for the outcome of pain at the hip or thigh. When a certain study [ 20 ] resulting in heterogeneity was removed, no heterogeneity was found in the remaining studies (RCTs: chi 2 = 0.83, df = 1, P = 0.36, I 2 = 0%; observational studies: chi 2 = 0.11, df = 2, P = 0.95, I 2 = 0%; total: chi 2 = 0.95, df = 4, P = 0.92, I 2 = 0%; Fig S 1 ), which could be explained by the different surgical skills of the surgeons between included studies. In addition, considering the length of follow-up time may have an impact on the complications of patients, by excluding 1 study with shorter follow-up time [ 22 ], it can be found that the heterogeneity has not changed significantly, which proves that the statistical results are reliable.…”
Section: Resultsmentioning
confidence: 99%
“…By synergistically altering the PSA and theanteversion angle, TAD can be easily adjusted to be less than 25 mm (20.52 ± 2.80 mm) which is recommended by several scholars during the fixation of IEFs in order to prevent complications [ 24 , 25 ]. The accessibility and perfection of TAD adjustment in our study smoothed the surgery (shorter operative time: 65.82 ± 11.16 min vs 79.50 ± 21.12 min [ 21 , 26 , 27 ] and fluoroscopy time: 2.03 ± 0.79 min vs 2.9 ± 0.16 min) [ 7 ]), improved the treatment effects (higher HHS: range, 57–89 vs 36–97 [ 28 ]) and decreased the complications (rate: 12.00%, 6/50 vs 57.44%, 108/188 [ 21 ]; cut-out: 0% vs 4% [ 29 ] or 2.7% [ 30 ]) compared with previous studies where TAD was higher than 25 mm, even modified 30 mm [ 31 ] in some cases [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%